Tangible and Intangible Values of a CRP: A Cost-Benefit Analysis. Issue 2 (3rd April 2022) - Gerber, William MPA; Hune, Nicole D.; Wang, Eugene W.; Kimball, Thomas G.
ABSTRACT: Collegiate Recovery Program (CRP) growth is dependent upon research that addresses the value of CRPs. Given that CRP research is relatively new, there are barriers related to justifying the establishment and growth of CRPs. One barrier to CRP expansion is the lack of cost-benefit analyses within the field. Understanding students and their wellbeing with CRPs is a focal point overshadowing the importance of financial implications even though finances are integral to CRP health and longevity. Thus, it is imperative to identify these financial implications in order establish and convey the value of a CRP. This article reports on a cost-benefit analysis completed using the national averages of cost and benefits related to CRPs. Findings reinforce the value of CRPs and show the monetary impact a CRP can add to an institution of higher learning. This cost-benefit analysis was developed for institutions of higher education using available national data. Conclusions, limitations, and future implications are discussed. In addition, a cost-benefit tool was developed to be utilized by those who wish to develop a CRP.